التسويق الدولي كأداة للتنمية الصادرات الزراعية دراسة قياسية لحالة الجزائر للفترة 1990-2023 - فرحاتي عبد الحفيظ; غدايري زهير; مهاني محمود (university of eloued جامعة الوادي, 2025)
"الملخص تهدف هذه الدراسة إلى قياس أثر التسويق الدولي في تنمية الصادرات الزراعية لدولة الجزائر خلال الفترة الممتدة من 1990 إلى2023،باستخدام نموذج الانحدار الذاتي للفجوات الزمنية الموزعة ARDL وقد تم الاعتماد على مجموعة من المؤشرات الكلية المعبرة عن التسويق الدولي والمتمثلة في : الإنتاج الزراعي، العاملون في الزراعة، الأراضي الزراعية، القيمة المضافة في الزراعة ، جودة الصادرات،مؤشر التنافسية الصناعية، جودة الصادرات، سعر الصرف، مؤشر الإنفتاح الإقتصادي، العبء الضريبي، تركز الصادرات، البنية التحتية ،التكنولوجيا و الإتصال، أما فيما يتعلق بمتغير صادرات المنتجات الزراعية فقد تم اختيار مؤشرين هما: الصادرات الزراعية، اختراق أسواق التصدير. و أظهرت النتائج وجود علاقة معنوية بين اغلب المتغيرات المدروسة و صادرات المنتجات الزراعية باستثناء مؤشرات مثل مؤشر البنية التحتية و التكنولوجيا المعلومات والاتصال وجودة الصادرات التي لم تظهر تاثيرا دالا . و توصي الدراسة بتطوير السياسات التسويقية و تفعيل أدوات الدعم المؤسساتي و اللوجستي لتحسين اختراق المنتجات الزراعية للأسواق الدولية. "Abstract This study aims to measure the impact of international marketing on the development of the Algerian agricultural exports over the period from 1990 to 2023, using the Autoregressive Distributed Lag (ARDL) model. A set of aggregate indicators representing international marketing were used, including agricultural production, agricultural workers, agricultural land, value added in agriculture, export quality, industrial competitiveness index, export quality, exchange rate, economic openness index, tax burden, export concentration, information and communication technology (ICT) infrastructure. Regarding the variable of agricultural product exports, two indicators were selected: agricultural exports and export market penetration. The results showed a significant relationship between most of the studied variables and agricultural product exports, with the exception of indicators such as the infrastructure index, information and communication technology (ICT), and export quality, which did not demonstrate a significant impact. The study recommends developing marketing policies and activating institutional and logistical support tools to improve the penetration of agricultural products into international markets.
ماستر تجارة
Keywords: تسويق الدولي; منتجات زراعية; صادرات زراعية; اختراق أسواق التصدير; نموذج ARDL; : International Marketing – Agricultural Products – Agricultural Exports – Export Market Penetration – ARDL Model